Investigation of Pavement Condition at Jalan Kampung Jawa, Pagoh, Johor - Anuar, Azhan Haziq; Abdur Rahim, Muhammad Syahmi Muhammad Shaiful; Ahmad, Muhammad Amir Ajwad; Bujang, Hazirah (Multidisciplinary Applied Research and Innovation, 2025)
Pavement distress encompasses a range of deteriorations in road surfaces, impacting their structural integrity and performance. The distresses can arise from factors such as traffic loads, climate variations and inadequate construction practices. Effective identification and classification of pavement distress are essential for informed maintenance and rehabilitation strategies. Pavement Condition Index (PCI) is a numerical rating assesses the overall condition of a road or pavement infrastructure. It takes into account various distress types, such as cracking, rutting and surface irregularities. PCI values range from 0 to 100, with higher scores indicating better pavement conditions. The PCI method was evaluated on Jalan Kampung Jawa, Pagoh, which has a length of 2km. The goals of this study are to analyze the factors that affect pavement distress, to evaluate pavement condition at Kampung Jawa, Pagoh and to propose the types of maintenance required for the road. To assess the pavement condition, the road was divided into 10 sections first, each with a length of 200m. At the conclusion of the study, the results indicate that sections 4, 5, 6, and 8 are in good condition, with a PCI rating of 86-100, followed by sections 7 and 9, which have a satisfactory condition rating of 71-85. While on the other hand, section 10 is in poor condition, with a PCI rating of 45-55. Sections 2 and 3 exhibit a very poor condition, with a PCI rating of 26-44, and finally, section 1 is deemed to be in a serious condition, with a PCI rating of 11-25. It is noteworthy that none of the sections in this study are categorized as fair or failed.